Fixed BMI eligibility criteria for GLP-1 receptor agonist trials and estimated trial-eligible proportions in Asian and non-Asian populations: A cross-sectional analysis - Ki Young Huh; Ildae Song (PLoS ONE, 2026)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are globally developed for metabolic diseases, yet clinical trials have underrepresented Asian populations who develop metabolic complications at lower body mass index (BMI) values than Non-Asian populations. This cross-sectional study characterized eligibility criteria in 352 GLP-1 RA trials registered on ClinicalTrials.gov (2017–2020) and estimated the proportion of populations meeting these criteria using nationally representative health survey data from 23,251 adults (5,984 Non-Asian US, 353 Asian US, and 16,914 Korean) from National Health and Nutrition Examination Survey (NHANES, US) and Korean NHANES (2021–2023). Mean BMI was substantially higher in Non-Asian US adults (29.8 kg/m 2 ) compared with Asian US (24.9 kg/m 2 ) and Korean (24.2 kg/m 2 ) populations. BMI criteria, specified in 233 trials (66.2%), demonstrated the largest eligibility disparities. For trials requiring BMI ≥ 30 kg/m 2 , eligibility was 41.5% for Non-Asian US versus 13.5% for Asian US and 7.2% for Korean adults. In contrast, HbA1c, eGFR, and liver function criteria showed minimal between-population differences (all > 93% meeting typical thresholds). These findings suggest that fixed BMI eligibility criteria are associated with substantially lower estimated trial-eligible proportions among Asian populations, supporting further evaluation of ethnicity-sensitive BMI thresholds in future GLP-1 RA trial design.